Analysis of the socio-environmental management of Covid 19 in Peru - Cueto Ramirez, Sandra Valeri (2021)
The objective of this article is to analyze the management of Covid-19 from a socio-environmental perspective, with a scientific, holistic and adaptive approach. On March 16 of 2020, the Peruvian government began to implement measures to slow the spread of the virus and allow time to strengthen the public health system and after 9 months the results have placed the country among the first places in the mortality rate world level. The basic lines of action of the Peruvian government have been focused on: reducing crowds, stocking up with hospital supplies and detecting infected. However, we identified that the actions corresponding to such basic lines lacked scientific support, were academically biased and inappropriate to the context. Our analysis has been accompanied by proposals that should have been applied in the initial phase of the proliferation of the virus, each of these proposals are designed based on scientific interdisciplinarity and adapted to the geographical and cultural heterogeneity of Peru. It is concluded that decision making must be in accordance with the different realities of the country and that since it is a diverse country, these decisions must be approached seeking the benefit of the entire population.